Effectiveness of Pipelle as Endometrial Sampling Procedure in Comparison with Dilatation and Curettage - Tahira Rasheed, Lubna Yasmeen (Journal of Rawalpindi Medical College, 2012)
Background: To determine safety and effectiveness of pipelle for taking endometrial biopsy as out patient procedure in comparison with dilatation and curettage (D&C). Methods: In this comparative study, detailed clinical evaluation of 80 patients was done to establish indication for endometrial sampling. Subjects were divided into 2 groups.In 1st group pipelle (n=40)procedure was performed as outpatient procedure without analgesia under aseptic conditions.Biopsies were taken and sent for histopathology and for acid fast bacilli in cases of infertility .Subjects were retained for 30 min to observe for any complication. In 2nd group (n=40) patients were admitted from out patient department and D&C done on very next day in operation theatre as formal procedure under anaesthesia .Patients were retained in ward after procedure to observe any post operative complications for one day. Samples were sent for histopathology . Chi Square test was used for statistical analysis. Results: There was no case of perforation in both groups.In first group of Pipelle 36 cases had no pain.When compared to second group statistical significance was .000. Mild bleeding was observed in 2 cases of pipelle as compared to 4 cases of 2nd group. Sample was adequate in 37 cases of pipelle while in 39 cases of D&C .Histopathology report when compared in 2 groups showed statistical significant difference was 0. 05. Conclusion: Endometrial Biopsy with Pipelle is safe, efficient and cost effective means of evaluating uterine endometrium It is associated with minimal discomfort, adequate sampling without need of anaesthesia.